MADRASAH SEBAGAI LEMBAGA PENDIDIKAN ISLAM DI INDONESIA - Adek Kholijah Siregar (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Madrasah is one of the educational institutions in Indonesia that has animportant role in the development of Madrasah education is generally established by the community, where the managers and support communities that determine the vision and mission whether the educational institutions have a desire to move forward. Madrasah is also a kind of education that gives attention and once makes the teachings of Islam as knowledge for the study program that held it. Madrasahs are educational institutions born from, and to the community. Complaints about the quality of education in madrasah are always not about lack of religious education, but rather the lack of general education that is not commensurate with public schools and has no social effect in society.Keywords: Madrasah, Islamic Education Agency